Engineering of monosized lipid-coated mesoporous silica nanoparticles for CRISPR delivery. (15th September 2020) - Noureddine, Achraf; Maestas-Olguin, Angelea; Saada, Edwin A.; LaBauve, Annette E.; Agola, Jacob O.; Baty, Keoni E.; Howard, Tamara; Sabo, Jennifer K.; Espinoza, Cindy R. Sandoval; Doudna, Jennifer A.; Schoeniger, Joseph S.; Butler, Kimberly S.; et al.
Abstract: CRISPR gene editing technology is strategically foreseen to control diseases by correcting underlying aberrant genetic sequences. In order to overcome drawbacks associated with viral vectors, the establishment of an effective non-viral CRISPR delivery vehicle has become an important goal for nanomaterial scientists. Herein, we introduce a monosized lipid-coated mesoporous silica nanoparticle (LC-MSN) delivery vehicle that enables both loading of CRISPR components [145 µg ribonucleoprotein (RNP) or 40 µg plasmid/mg nanoparticles] and efficient release within cancer cells (70%). The RNP-loaded LC-MSN exhibited 10% gene editing in both in vitro reporter cancer cell lines and in an in vivo Ai9-tdTomato reporter mouse model. The structural and chemical versatility of the mesoporous silica core and lipid coating along with framework dissolution-assisted cargo delivery open new prospects towards safe CRISPR component delivery and enhanced gene editing. Statement of significance: After the discovery of CRISPR gene-correcting technology in bacteria. The translation of this technology to mammalian cells may change the face of cancer therapy within the next years. This was first made possible through the use of viral vectors; however, such systems limit the safe translation of CRISPR into clinics because its difficult preparation and immunogenicity. Therefore, biocompatible non-viral nanoparticulate systems are required to successfully deliver CRISPR into cancer cells. The present study presents the use of biomimetic lipid-coated mesoporous silica nanoparticles showing successful delivery of CRISPR ribonucleoprotein and plasmid into HeLa cervical and A549 lung cancer cells as well as successful gene editing in mice brain. Graphical abstract: Image, graphical abstract